Development of Correlation between Soaked CBR and In-Situ CBR Determined by DCP for Soil in the Southern Province of Rwanda - NTIRENGANYA, Naphtal; Basher, Babiker; Suliman Ahmed, Elsir; Shallal, Dr. Mohammed (International Journal of Scientific Research and Management (IJSRM), 2020)
In this paper, using Dynamic Cone Penetrometer (DCP), in-situ CBR tests have been carried out on 31 locations in Nyamgabe District in the Southern Province of Rwanda. The in-situ CBR results have been obtained from these tests. Thirty One tests pits were dug in the same locations and samples taken to the laboratory. Sieve Analysis, Atterburg Limits, Proctor and CBR tests were conducted on these samples. Accordingly a correlation has been developed between the In-Situ CBR using the DCP and the laboratory soaked CBR. The developed correlation helps to estimate the laboratory soaked CBR from the in-situ CBR using the DCP